Triage in preventive child healthcare: a prospective cohort study of care use and referral rates for children at risk. Issue 10 (30th October 2017) - Bezem, Janine; Kocken, Paul L; Kamphuis, Mascha; Theunissen, Meinou H C; Buitendijk, Simone E; Numans, Mattijs E
Abstract : Objectives: A novel triage approach to routine assessments was introduced to improve the efficiency of Preventive Child Healthcare (PCH): PCH assistants carried out pre-assessments of all children and sent the children with suspected health problems to follow-up assessments conducted by a physician or nurse. This two-step approach differed from the usual approach, in which physicians or nurses assessed all children. This study was aimed to examine the impact of triage and task shifting on care for children at risk identified by PCH or parents and schools. Design and participants: An observational prospective cohort design was used, with an analysis of the basic registration data from the preventive health assessments for 1897 children aged 5 to 6, and 10 to 11, years from a sample of 41 schools stratified by socioeconomic status, region of PCH service and urbanisation. Setting: A comparison was made between two PCH services in the Netherlands that used the triage approach and two PCH services that provided the usual approach. Main outcome measures: The primary outcome measures were the referral rates to either additional PCH assessments or external services. The secondary outcome measures were the rates of PCH assessments requested by, for example, parents and schools. Results: Overall, a higher referral rate to additional PCH assessments was found for the triage approach than for the usual approach (OR 1.3, 95% CI 1.0 to 1.6), mainly in the age group of 5 to 6 years (OR 1.9, 95% CI 1.3 to 2.7). We found a lower rate of referral to external services in the triage approach (OR 0.4, 95% CI 0.3 to 0.7) and a higher referral rate to PCH assessments on request (OR=4.6, 95% CI 3.0 to 7.0). Conclusions: The triage approach provides extra opportunities to deliver PCH assessments and PCH assessments on request for children at risk. Further research is needed into the cost benefits of the triage approach.